Optical properties of solutions of nanopowders magnetite and stanum dioxide - T. N. Zaitseva; A. V. Nosarev; B. G. Ageyev; L. V. Kapilevich; Ye. Yu. Diyakova; A. A. Magayeva; O. G. Terekhova; V. I. Itin (Бюллетень сибирской медицины, 2010)
Optimal concentrations of the magnetite and stanum dioxide nanopowders for production of a stable aerosol are determined. The dependence of laser radiation absorption by the aerosol on the nanomaterial concentration in the initial solution is revealed.